TFEB, a master regulator of lysosome biogenesis and autophagy, is a new player in alcoholic liver disease - Bala, Shashi; Szabo, Gyongyi (Digestive Medicine Research, 2018)
Lysosomes play a major role in cellular metabolism and human health. Lysosomes are main catabolic organelles of the cell and play a central role in cellular processes including autophagy, plasma membrane repair, cellular clearance and cell signaling (1). Lysosomal dysfunction has been associated with several diseases including degenerative disorders of the brain and muscular system (1).